2022
DOI: 10.1029/2021ef002583
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Land‐Neutral Negative Emissions Through Biochar Sequestration

Abstract: Negative emissions (NE) are under discussion as elements of mitigation strategies aiming to achieve the climate targets of the Paris Agreement. However, biomass‐based NE technologies such as bioenergy with carbon capture and storage (BECCS) require vast land areas in order to meet the targets projected by climate economic optimization models, thereby competing with food production and ecosystem protection. Here we assess feasible NE contributions of alternative, more sustainable pyrogenic carbon capture and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…The primary "removal" is carried out by photosynthesis while pyrolysis slows down the return to the atmosphere. Pyrolysis with carbon capture and storage (PyCCS, in biochar) has cobenefits for food and fiber production ([101] and metastudies therein); yield improvements have particularly been found in subtropical and tropical soils which could make this form of CDR land-neutral [102]. Adding biochar to organic waste treatment such as composting can reduce gaseous N emissions [103,104].…”
Section: Mitigation Options To Reach Carbon Neutralitymentioning
confidence: 99%
“…The primary "removal" is carried out by photosynthesis while pyrolysis slows down the return to the atmosphere. Pyrolysis with carbon capture and storage (PyCCS, in biochar) has cobenefits for food and fiber production ([101] and metastudies therein); yield improvements have particularly been found in subtropical and tropical soils which could make this form of CDR land-neutral [102]. Adding biochar to organic waste treatment such as composting can reduce gaseous N emissions [103,104].…”
Section: Mitigation Options To Reach Carbon Neutralitymentioning
confidence: 99%
“…Pyrogenic carbon capture and storage, which includes the production and pyrolysis of biomass and the application of biochar to soils and materials, has been identified as one of the most promising negative emission technologies (Smith et al, 2019;Werner et al, 2018Werner et al, , 2022. To establish a carbon sink, CO 2 must be removed from the atmosphere, transformed into a stable form, and stored for a verifiable long time.…”
Section: Carbon Sinkmentioning
confidence: 99%
“…In fact, the storage of carbon is successful in the long term, i.e., it is not released into the air as CO 2 . Therefore, in the case of biogenic feedstock, it is removed from the atmosphere, achieving a "negative emission" (Werner et al, 2022).…”
Section: Strengths (Characteristics Of the Technologies That Give It ...mentioning
confidence: 99%
“…V reiro et al 2018;Werner et al 2022) or as biochar-functionalized materials in other sectors. The risk of heavy metal contamination in soils and their potential transfer to the food chain may also be reduced following conversion to biochar, which makes it safer for land application (Marchuk et al, 2021).…”
mentioning
confidence: 99%